Parametric Represantations of Surfaces Containing a Common Isophote Curve In 3-Dimensional Galilean Space - ŞEYDA ÖZEL; Mehmet Bektaş (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This paper investigates a family of defined surfaces that share a common isophote curve in three‑dimensional Galilean space. By employing a given curve in this space with its Frenet frame we derive characterizations of the surfaces and present illustrative examples where in the curve functions, as an isophote.